A prevalence study of the relationship between indoor workplace temperature and employee's health in Marriott Resort Miri - Lin, Khi Liang (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This is a study that examine the relationship between indoor workplace temperature and employee's physical health in Marriott resort Miri. The research highlights the relationship between extreme hot, standard and extreme cold indoor workplace temperature with the employee's physical health based on the frequency that they experiences the temperature related illness symtopms . The design of this research is using a self-administered questionnaire 100 employees from one organization was surveyed in order to examine the three main hypotheses of the research. And the fmdings of the study shows that the results revealed that extreme cold and extreme hot indoor workplace temperature does not have significant relationship with the employees health within the organization. Moreover the practical implications ofthe study is by using the theoretical and managerial implications of the results, are also discussed in this research, together with the recommendations for managing indoor workplace temperature and employees physical health. The research examines the above mentioned links for the first time in the Marriott resort Miri branch, Malaysia Sarawak context. And suggestions for future research are discussed.